Assessing and improving spatial ability for design based disciplines utilising online systems : critical success factors report. - Sutton, Ken; Allen, Rebecca (Australian Learning and Teaching Council, 2011)
Report from a project that investigated the assessment and improvement of spatial ability for design-based higher education disciplines utilising online systems. An online psychometric test of spatial ability (the 3D Ability test) was developed specifically for design-based disciplines. A series of online interactive 3D learning tasks designed to improve spatial skills are were used. The learning tasks included remediation options for poor performers and purpose-designed gender neutral activities to address the gender bias in spatial performance. This report focuses on critical success factors.